Kritik Atas Eksplanasi Deduktif-Nomologis dalam Ilmu Sejarah - Heri Santoso; Cuk Ananta Wijaya (Jurnal Filsafat "WISDOM", 2003)
The critical philosophy of history or the scientific philosophy of history is deal with how historians reconstruct the pas event. Historians in their attempt to explain the pas event, according to the historian philosophers, are able to use of the deductive pattern of explanation. Researcher wants, in the first instance, to explore and reflect the concept of deductive nomological explanation, as it was suggested by Carl Gustav Hempel, William Dray, and Ernest Nagel, and it is implemented in history. Secondly, it wants to criticize and give a way out of the deductive nomological explanataion that is applied in history